Self-Adjustment in Modern Islamic Boarding Schools: A Study of Self-Regulation and Religiosity among Students - Anisah Triyuliasari; Ali Syahidin Mubarok (Faculty of Psychology, Sunan Gunung Djati Islamic State University of Bandung, 2024)
A student in general definitely needs adjustment to the new environment in his boarding school. Where this will be a challenge for them to be able to adjust to the existing. This study aims to determine the effect of self-regulation and religiosity on self-adjustment in female students at Pondok Modern Darul Hikmah.. This study used a causal-comparative quantitative method, with a sample size of 150 participants who were selected based on a purposive sampling technique. Data analysis in this study used multiple linear regression analysis techniques. The results of the hypothesis testing that has been done show R Square or a coefficient of determination of .321, which is interpreted that the variables of self-regulation and religiosity simultaneously have an impact on the self-adjustment variable. And based on the f test performed, it is known that the value of Sig. .000 <.05 indicates that self regulation and religiosity variables simultaneously affect self adjustment variables. Thus it can be concluded that simultaneously self-regulation and religiosity have an impact on self adjustment